LASER AS A DEVICE FOR MEASUREMENT OF THIN THREADS - A SCHOOL LABORATORY EXPERIMENT IN PHYSICS - Deneva, Hristina; Lazov, Lyubomir; Teirumnieka, Erika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The physics of the last century is included in all EU curricula and emphasis in education is shifted from content to the forms, methods and means of teaching and learning. Different kinds of lessons (including laboratory classes) and their didactic structure are subject to the understanding, adoption and creating conditions to build motivation to learn physics and astronomy, active utilization of physical knowledge and building cognitive and practical skills. Performance of demonstration and laboratory classes using a laser device is a type of teaching strategy to good education in physics. Properties of laser light as observation, classification, communication, drawing conclusions, planning, interpretation and forecasting, are particularly suitable when monitoring and studying the phenomena of interference and diffraction. Through both qualitative and quantitate ways, in this paper is presented a physical experiment for measurement of thin threads in a High school from students. Experimental skills will enhance interest in physics and especially to modern applications of laser devices, as well as career guidance of students.